2005
DOI: 10.1111/j.1747-0765.2005.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Stainability of Root-Tip Protoplasts as an Indicator of Aluminum Tolerance in a Wide Range of Plant Species, Cultivars and Lines

Abstract: We previously developed a new simple technique of methylene blue (MB) staining for the discrimination of aluminum (Al)‐tolerant protoplasts from 4 plant species (rice, oats, maize and pea). The objectives of the present study were to confirm the applicability of this technique to a wider range of plant species, cultivars and lines, and to identify a common strategy for the early stage of Al tolerance. A total of 10 plant species, two Brachiaria spp., two Oryza spp., buckwheat, maize, pea, triticale, wheat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…In root length, 63 accessions (78.75%) showed significant Al induced stress and 23 (28.75%) in fresh weight, while no distinct and visible symptom of aluminium toxicity were observed in the shoot of finger millet genotypes (Figure 2). High root length inhibition was reported in pigeon pea on 20 µM AlCl 3 (Choudhary et al, 2011) and in maize at 20 µM (Wagatsuma et al, 2005). The present study also confirmed the inhibition of root growth at 112.5 µM due to aluminium phytotoxicity.…”
Section: Characterization Of Ethiopian Finger Millet For Aluminium Tosupporting
confidence: 86%
“…In root length, 63 accessions (78.75%) showed significant Al induced stress and 23 (28.75%) in fresh weight, while no distinct and visible symptom of aluminium toxicity were observed in the shoot of finger millet genotypes (Figure 2). High root length inhibition was reported in pigeon pea on 20 µM AlCl 3 (Choudhary et al, 2011) and in maize at 20 µM (Wagatsuma et al, 2005). The present study also confirmed the inhibition of root growth at 112.5 µM due to aluminium phytotoxicity.…”
Section: Characterization Of Ethiopian Finger Millet For Aluminium Tosupporting
confidence: 86%
“…At Al concentration of 150 µM and above, the growth of roots of all the varieties were greatly hampered to the extent that there was nearly no difference among them. These data were somewhat similar to previous observations relating inhibition of root elongation with increased Al concentrations in the growth medium (Echart et al, 2002;Wagatsuma et al, 2005;Choudhary et al, 2011). The conclusion was that under the defined growth conditions, Al toxicity would likely begin with an Al concentration in the solution higher than 50 µM (Figure 3).…”
Section: Optimizing Threshold Toxicity Level Of Al On Finger Millet Vsupporting
confidence: 81%
“…Similar Al sensitivity was identified in rice (Oryza sativa) containing greater amounts of phospholipid in the PM (Khan et al, 2009). Although PM lipid composition may affect Al tolerance via other mechanisms such as Al permeability (Wagatsuma et al, 2005;Ryan et al, 2007), PM surface negativity associated with P recycling is a factor that influences Al tolerance in some plant species and varieties.…”
Section: Discussionmentioning
confidence: 99%